Dietary traits of the ungulates from the HWK EE site at Olduvai Gorge (Tanzania): Diachronic changes and seasonality. Issue 120 (July 2018) - Rivals, Florent; Uno, Kevin T.; Bibi, Faysal; Pante, Michael C.; Njau, Jackson; de la Torre, Ignacio
Abstract: The Oldowan site HWK EE (Olduvai Gorge, Tanzania) has yielded a large fossil and stone tool assemblage at the transition from Lower to Middle Bed II, ∼1.7 Ma. Integrated tooth wear and stable isotope analyses were performed on the three most abundant ungulate taxa from HWK EE, namely Alcelaphini, cf. Antidorcas recki (Antilopini) and Equus oldowayensis (Equini), to infer dietary traits in each taxon. Some paleodietary changes were observed for cf. A. recki and E. oldowayensis based on tooth wear at the transition from the Lemuta to the Lower Augitic Sandstone (LAS) interval within the HWK EE sequence. Stable carbon and oxygen isotope data show no significant changes in bulk diet or hydroclimate between the Lemuta and LAS intervals. The combined tooth wear and stable isotope data suggest similar paleoecological conditions across the two HWK EE intervals, but that differences in vegetation consumed among ungulates may have resulted in changes in dietary niches. Integrating tooth wear and stable isotope analyses permits the characterization of ungulate diets and habitats at HWK EE where C4 dominated and minor mixed C3 and C4 habitats were present. Our results provide a better understanding of the paleoenvironmental conditions of the Lemuta and LAS intervals. The LAS assemblage was mostly accumulated during relatively dry periods at Olduvai Gorge when grasses were not as readily available and grazing animals may have been more nutritionally-stressed than during the formation of the Lemuta assemblage. This helps to contextualize variations in hominin and carnivore feeding behavior observed from the faunal assemblages produced during the two main occupations of the site.